THE INTERACTIVE ROLE OF THE QUALITY OF WORKING LIFE IN THE RELATIONSHIP BETWEEN PROFESSIONAL COMPATIBILITY AND CAREER CREATIVITY - Lecturer. Dr. Jasim Saad Jasim (Proximus Journal Publishing, 2024)
The main research problem was represented by the gap between the intellectual understanding of the variables and the field reality of the university under study, as universities in Iraq in general and the University of Dhi Qar under study suffer from several problems, including at the level of their location and competition with other universities, and at the level of performing their duties towards beneficiaries, as these problems cause a decrease in the level of performance of their tasks as a result of either laws and ministerial instructions or as a result of the lack of capabilities and skills required to accomplish their functions by dealing with and managing things at the University, and the aim of this research is to study the influential relationship of the quality of working life in crystallizing the relationship between professional compatibility and career creativity measuring levels The research was conducted on the teachers assigned administrative tasks at the head of the University of Dhi Qar, who were deliberately selected, where (214) questionnaires were distributed, designed by the researcher, and after analyzing the results, it became clear that the quality of working life has an impact on the relationship between professional compatibility and career creativity at the level of professional compatibility of the individual with his the most important recommendations are to focus on internal working conditions by working on Establishing solid rules to enhance their levels and the level of work and awareness by teachers by building an organizational culture based on the development of physical and psychological work requirements and enhancing professional compatibility, which is one of the important indicators in the quality of performance of finding factors of adaptation of teaching to the internal and external environments .
Keywords: The quality of working life; Professional compatibility; Career creativity